The effectiveness of spinal cord stimulation combined with physiotherapy in the management of chronic pain in adults: a systematic review - Barros, Adilia Maria Soares Porciuncula; Pereira, Gabrielly Santos; Silva, Josie Resende Torres da; Silva, Marcelo Lourenço da; Costa e Silva, Maria do Desterro da; Ferrera, Luciano Maia Alves (Frontiers in Pain Research, 2025)
BackgroundChronic pain affects a significant portion of the population, and conventional treatments often prove insufficient. Spinal Cord Stimulation (SCS), a neuromodulation technique, has shown benefits in pain relief, while physiotherapy is widely employed to enhance physical function and quality of life. Although the combination of these approaches may offer synergistic effects, existing evidence is limited and fragmented.ObjectiveThis systematic review aimed to evaluate the clinical outcomes of Spinal Cord Stimulation (SCS), with or without the association of physiotherapy, in the management of chronic pain in adults. Methodology: The review was conducted following PRISMA guidelines and the PICO strategy. A comprehensive search was performed across databases including Cochrane Library, ScienceDirect, BASE, and VHL (BVS: MEDLINE, IBECS, WPRIM, LILACS, PERIÓDICO CAPES) using MeSH terms and Boolean operators: (“Spinal Cord Stimulation” OR “Neuromodulation”) AND (“Chronic Pain” OR “Pain Management”) AND (“Physical Therapy Modalities” OR “Physiotherapy” OR “Rehabilitation”). Only studies published in English, Spanish, or Portuguese in the past 10 years were included, focusing on chronic pain and reporting outcomes related to pain reduction and functional improvement.ResultsEight studies comprising 777 patients were included. Spinal cord stimulation alone led to significant pain reductions, with responder rates above 80% and average decreases of 5–6 cm on pain scales. Improvements in quality of life and functional disability were also reported, with reductions of over 30 points in disability indices and up to 40% in opioid use. However, only one study included physiotherapy as a complementary intervention, without isolating its effects. No study directly evaluated the combined efficacy of SCS and physiotherapy, highlighting a gap in the literature.ConclusionThe findings highlight the proven effectiveness of SCS in chronic pain management but reveal a lack of studies assessing its integration with physiotherapy. Future clinical trials should address this gap to explore potential synergistic effects and optimize interdisciplinary pain treatment strategies.